Investigation of delta modulation of speech for mobile radio - Karim, M.R. (Institute of Electrical and Electronics Engineers (IEEE), 1982)
A characteristic of a mobile radio channel is the occurrence of correlated signal fading that results in burst errors. The use of adaptive delta modulation (ADM) based on explicit transmission of the quantizer step size was proposed earlier for speech communication over such a channel. Two other vaiable step-size delta modulation (VSDM) schemes are presented, and their performance in a mobile radio environment is discussed. One of them is the constant factor delta modulation that uses one-bit memory and produces fast and instantaneous step-size changes. The other is the digitally controlled delta modulation (DCDM) that incorporates a new step-size adaptation strategy using seven bits of memory.